2013
DOI: 10.1111/vop.12028
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the use of spectral domain optical coherence tomography (SDOCT) for evaluation of the healthy and pathological cornea in dogs and cats

Abstract: SD-OCT examination of normal and pathological corneal conditions in dogs and cats gave an accurate evaluation of each component of the cornea. The advantage of the technique is the in vivo, real-time evaluation of all corneal layers with the absence of corneal contact. Constraints included the necessity of sedation for precise focus and the low quality of images obtained with too pigmented or thickened corneas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
51
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 29 publications
11
51
1
1
Order By: Relevance
“…Anterior segment imaging is a rapidly advancing field and is increasingly being utilized in physician‐based ophthalmic practices for a number of purposes including planning for photorefractive surgery, monitoring corneal diseases including keratoconus, measuring anterior chamber depth, and assessing narrowing of the iridocorneal angle (ICA) . Anterior segment imaging using OCT has recently emerged in canine research and is expected to be useful in clinical patients as well . A recent case series confirmed that this technique is applicable to the evaluation of the canine and feline cornea in healthy and pathological conditions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anterior segment imaging is a rapidly advancing field and is increasingly being utilized in physician‐based ophthalmic practices for a number of purposes including planning for photorefractive surgery, monitoring corneal diseases including keratoconus, measuring anterior chamber depth, and assessing narrowing of the iridocorneal angle (ICA) . Anterior segment imaging using OCT has recently emerged in canine research and is expected to be useful in clinical patients as well . A recent case series confirmed that this technique is applicable to the evaluation of the canine and feline cornea in healthy and pathological conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Anterior segment imaging using OCT has recently emerged in canine research and is expected to be useful in clinical patients as well . A recent case series confirmed that this technique is applicable to the evaluation of the canine and feline cornea in healthy and pathological conditions . FD‐OCT and TD‐OCT have both recently been used for imaging and quantification of corneal, limbal, and bulbar conjunctival epithelial thickness in healthy humans .…”
Section: Introductionmentioning
confidence: 99%
“…In the veterinary ophthalmic literature, the use of OCT was first reported in 2007 in a study evaluating retinal structure in the cat and in 2008 to describe the retinopathy of the Coton de Tulear dogs . Recently, several studies have used OCT to characterize the normal cornea, iridocorneal angle, and retina in several species, as well as corneal abnormalities in dogs and cats . In the majority of these studies, the animals were under general anesthesia or deep sedation to avoid eye movement during imaging …”
Section: Introductionmentioning
confidence: 99%
“…Bullous keratopathy (BK) is a corneal disease caused by endothelial decompensation due to endothelial dystrophy, trauma or glaucoma (Pires et al 1999, Maggs et al 2013, which leads to stromal epitelial edema and a subepithelial bullae formation (Famose 2014). The etiology and pathogenesis of feline bullous keratopathy is unknown (Glover et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The available surgical options include keratectomy and keratoplasty, conjunctival flaps, tarsorraphy, collagen cross-linking and the amniotic membrane transplantation (Pires et al 1999, Ortiz et al 2011, Maggs et al 2013, Zhao et al 2013, Spiess et al 2014, Pot et al 2015, Famose 2014.…”
Section: Introductionmentioning
confidence: 99%